Featuring Mistakes: The Persuasive Impact of Purchase Mistakes in Online Reviews. (January 2020) - Reich, Taly; Maglio, Sam J.
Companies often feature positive consumer reviews on their websites and in their promotional materials in an attempt to increase sales. However, little is known about which particular positive reviews companies should leverage to optimize sales. Across four lab studies involving both hypothetical and real choices as well as field data from a retailer's website (Sephora), the authors find that consumers are more likely to purchase a product if it is recommended by a reviewer who has (vs. has not) made a prior purchase mistake. The authors define a purchase mistake as a self-identified suboptimal decision whereby people purchase a product that subsequently fails to meet a threshold level of expected performance. This persuasive advantage emerges because consumers perceive reviewers who admit a purchase mistake as having more expertise than even reviewers whose purchase experience has not been marred by mistakes. As a result, in marketers' attempts to increase the persuasive influence of reviews featured in their promotional materials, they may inadvertently decrease it by omitting the very information that would lead consumers to be more likely to purchase recommended products.